Outbreak of acute gastroenteritis in an air force base in Western Greece - Kolokotronis Theodoros; Komninou Georgia; Venieri Danai; Jelastopulu Eleni; Constantinidis Theodoros C; Bantias Christos (BMC, 2006)
Abstract Background On the 20th September 2005, soldiers and staff at the Air Force base in Western Greece experienced an outbreak of acute gastroenteritis. The purpose of this study was to identify the agent and the source of the outbreak in order to develop control measures and to avoid similar outbreaks in the future. Methods A case-control analytical approach was employed with 100 randomly selected cases and 66 controls. Patients completed standardized questionnaires, odds ratios were calculated and statistical significance was determined using χ2 test. In addition, to identify the source of the infection, we performed bacteriological examination of food samples (included raw beef, cooked minced meat, grated cheese and grated cheese in sealed package) collected from the cuisine of the military unit. Results More than 600 out of the 1,050 individuals who ate lunch that day, became ill. The overall attack rate, as the military doctor of the unit estimated it, was at least 60%. The overall odds ratio of gastroenteritis among those who had lunch was 370 (95% CI: 48-7700) as compared to those who didn't eat lunch. Among the symptoms the most prominent were watery diarrhoea (96%) and abdominal pain (73%). The mean incubation period was 9 h and the median duration of the symptoms was 21 h. In the bacteriological examination, Staphylococcus aureus was detected in a sample of raw beef (2,000 cfu per g) and in two samples of grated cheese; leftover cheese from lunch (7,800 cfu per g) and an unopened package purchased from the market (3,000 cfu per g). Conclusion The findings of this study suggest that the aetiological agent of this outbreak was S. aureus. The food vehicle was the grated cheese, which was mixed with the beef and served for lunch in the military unit. This outbreak highlights the capacity of enterotoxin-producing bacteria to cause short term, moderately-severe illness in a young and healthy population. It underscores the need for proper food handling practices and reinforces the public health importance of timely notification of such outbreaks.